Discrepancy analysis in university curriculum evaluation - Mejia-Mejia, Elias; Díaz-Flores, Francis (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Curriculum evaluation in university education is crucial to improve the quality of professional education. This paper proposes a rubric to evaluate the university curriculum in order to obtain accurate information on its current state and to guide its restructuring according to the needs of updating and institutional demands. Emphasis is placed on the adoption of an objective methodological approach as opposed to subjective criteria. The methodology used, called "discrepancy analysis", is based on a theoretical model of an ideal curriculum with 10 components, each with a weighted value according to its importance. The evaluation of the curriculum is based on how close or far it is from this ideal model, reflecting its effectiveness and quality. The professional profile stands out as a fundamental source in the development of the curriculum, and must be relevant, comprehensive and consistent with the educational concept adopted by the institution. A rubric is presented to evaluate the professional profile in terms of coherence, relevance, completeness, clarity and structure. The constituent elements of the curriculum, such as the situational diagnosis, the doctrinal framework, the institutional decisions and the scope of work performance, are evaluated to ensure their alignment with the professional training objectives and the needs of the labor market. The organizational structure of the curriculum, the generation of curricular units, the design of the syllabus, the writing of summaries and the recommendations for the development of syllabi are crucial aspects that are evaluated to ensure the coherence and effectiveness of the university curriculum.